Maximizing Propylene Separation from Propane by Extractive Distillation with Aqueous N‐Methyl‐2‐pyrrolidone as Separating Agent. Issue 9 (4th August 2021) - Cruz Valdez, Jesús Alonso; Avilés Martínez, Adriana; Vallejo Montesinos, Javier; Pérez, Elías; Patiño-Herrera, Rosalba
Abstract: The separation of polymer‐grade propylene from a propylene‐propane mixture was performed by an extractive distillation (ED) process in the steady state, and was developed on the Aspen Plus V9 simulator, by using an extractive column and a recovery column. To increase the volatility and relative selectivity of propylene, aqueous N ‐methyl‐2‐pyrrolidone (NMP) was used as extracting agent. By using an ED process and aqueous NMP, compared with the high‐pressure binary distillation process, a reduction in energy consumption was obtained, with a saving of 52 % in total annual cost. Abstract : Production of high‐purity propylene is important due to its use as feedstock for numerous products. Herein, a simulated extractive distillation process with aqueous N ‐methyl‐2‐pyrrolidone as separating agent was used to separate polymer‐grade propylene from propane. Compared with the high‐pressure binary distillation process, it showed lower energy consumption and 52 % saving in total annual cost.